Повтори як засіб створення репрезентації національно-мовної картини світу (на матеріалі повісті М. Матіос «Солодка Даруся») - Пахолок, Зінаїда; Pakholok, Zinaida (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті аналіз повторів здійснено на матеріалі твору, присвяченого долі українців, котрі жили на Буковині. Зображено життя гуцулів у 30–70-ті роки ХХ ст. при різних окупаційних режимах, передано напружені стосунки, що існували між українцями й румунською, німецькою, радянською владами. Ідеться про загальнолюдське, морально-етичне: переломлення в психіці, світогляді, сприйнятті світу людей. Мовна одиниця з повтором розкриває глибинний зміст і функціональні можливості лише із застосуванням нової парадигми знань, яка ґрунтується на етнофіло¬софських, етнопсихологічних та етнокультурних підходах до мовного явища. The existing cultural and philosophical interpretation of language involves consideration of linguistic units which are based on the way of life and mentality of the nation, as the peculiarities of world view, mental structure and behavior due to national origin and ethnic community are reflected in language forms. Analysis of repetitions is carried out on the material of the story devoted to the fate of Ukrainians who were living in Bukovina. The author describes hutsuls in 30–70 years of the XX century during different occupation regimes, depicts tension relations that existed between the Ukrainian and Romanian, German, Soviet authorities; it is said about the universal, moral and ethical: breaking point in the psyche, worldview, and people’s perception of the world. The author managed to join present and past events by using inverse plot and repetition, the particular characteristics of which are rooted in lifestyle and behavioural stereotypes. Verbal formulas of doubling while performing semantic and structural features, also enhance the description of the characteristic of the protagonist or object, concept, transmit the frequency of action, and provide the text with expressiveness. The usage of different types of repetition leads to the appearance of keywords that represent the most important concepts of text and play a significant role in the perception of the work and interpretation of the meaning. Language unit with repetition reveals the deeper meaning and functionality only with the use of a new paradigm of knowledge based on the ethno-philosophical, ethno-psychological and ethno-cultural approaches to the language phenomenon.
Repetition as a Mean of Representation’s Creating of the National and Language Picture of the World (Based on the Story by M. Matios «Sweet Darusia»)
Keywords: повтор; ментальність; картина світу; концептосфера; повість; repetition; concept; mentality; world view; sphere of concepts; story